The genomic landscape of cohesin-associated chromatin interactions - DeMare, Laura E.; Leng, Jing; Cotney, Justin; Reilly, Steven K.; Yin, Jun; Sarro, Richard; Noonan, James P. (Genome Research, 2013)
Cohesin is implicated in establishing tissue-specific DNA loops that target enhancers to promoters, and also localizes to sites bound by the insulator protein CTCF, which blocks enhancer-promoter communication. However, cohesin-associated interactions have not been characterized on a genome-wide scale. Here we performed chromatin interaction analysis with paired-end tag sequencing (ChIA-PET) of the cohesin subunit SMC1A in developing mouse limb. We identified 2264 SMC1A interactions, of which 1491 (65%) involved sites co-occupied by CTCF. SMC1A participates in tissue-specific enhancer-promoter interactions and interactions that demarcate regions of correlated regulatory output. In contrast to previous studies, we also identified interactions between promoters and distal sites that are maintained in multiple tissues but are poised in embryonic stem cells and resolve to tissue-specific activated or repressed chromatin states in the mouse embryo. Our results reveal the diversity of cohesin-associated interactions in the genome and highlight their role in establishing the regulatory architecture of development.